Production of PDMS/PVDF thin film composite membrane for CO2/N2 separation - Norhidaya, Summah (2012)
In this thesis,a thin film composite(TFC)membrane was prepared for separation of carbon dioxide(CO2)and nitrogen (N2).The main purpose of this research is to study the performance of polydimethylsiloxane(PDMS) /polyvinylidene fluoride (PVDF) thin film composite membrane in term of permeability and selectivity.The support layer was fabricated from PVDF and the coating layer was prepared from PDMS at various concentrations which are 3,5,8 and 10 wt.% PDMS. The coating of the membrane was done by the dip coating method. The permeations and selectivity of the prepared membranes for CO2 and N2were tested using Gas Permeation Test under the pressure up to 2 bars. Parameters such as the concentration of PDMS on the coating layer and various feed pressures that influence the performances of the membranes were evaluated.The results indicated that the permeability of the membranes is decrease with increment of the concentration of PDMS on the coating layer but increase in term of selectivity.The test also shows the correlation between the feed pressure applied and the performance of the membrane.Increment in the feed pressure is increasing the selectivity and permeability of the membranes.The morphology of the membrane is characterized using Scanning Electron Microscopy(SEM)and the chemical component of the membrane is analysed by Fourier Transforms Infrared(FTIR). The analysis from the membrane characterization is supporting the performance of the membrane. Membrane with 10 wt.% PDMS concentration shows the best performance with high feed pressure.